Pengaruh Efektivitas Komite Audit, Bankruptcy Prediction, dan Solvabilitas terhadap Audit Delay - Altarisya, Viola; Nelvirita, Nelvirita (Jurnal Nuansa Karya Akuntansi, 2023)
This research analyzes the influence of audit committee effectiveness, bankruptcy prediction, and solvency on audit delays. This research uses annual reports on basic material sector companies listed on the Indonesian stock exchange for 2018-2022. The sampling technique used in this research is purposive sampling, with a total sample of 70 companies in 2018-2022. This study uses multiple linear regression analysis in hypothesis testing. The results showed that audit committee. The sample selection in this study used a purposive sampling technique. The research results show that the effectiveness of the audit committee and Bankruptcy prediction do not have a significant effect on audit delay. Meanwhile, solvency has a significant effect on audit delay.